Quantum and semiclassical Husimi distributions for a one-dimensional resonant system - Egydio de Carvalho, R. [UNESP]; De Aguiar, M. A M (American Physical Society (APS), 1992)
We compare exact and semiclassical Husimi distributions for the single eigenstates of a one-dimensional resonant Hamiltonian. We find that both distributions concentrate near the unstable fixed points even when these points are made complex by suitably varying a parameter. © 1992 The American Physical Society.